PENGEMBANGAN SOAL KETERAMPILAN PROSES SAINS PADA PEMBELAJARAN BIOLOGI SMA - Dyah Kesuma Ramadhani; Rahmi Susanti; Djunaidah Zen (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2015)
Abstract: Research about the development of Science Process Skills (SPS) has been carried out as SPS measuring instrument study materials in Biology subject at 11th grade of senior high school. The study is aimed to produce a valid and practical test instrument of SPS. The method used in this research is Development Research (DR) method which refers to the instrument development model from Djaali and Mulyono (2008). The steps of the research and development consist of several phases: synthesis theory and requirements analysis, design stage (variable construction, development of indicators, the preparation of the lattice matter, writing of instruments, scoring) and the evaluation phase. Evaluation phase is divided into three: validity test, reliability test and analysis of grain items. The analysis of grain items is done by analyzing the degrees of difficulty, different power and distracters function. The validation of Science Process Skills (SPS) is done in three stages, namely validation theoretical (content experts, constructs experts and linguists) and empirical validation (test participants' answers). Based on the theoretical validation of the results obtained an average value of 4.2 which indicates that the questions of SPS is valid. Practicality of SPS can be detected through the result analysis of the test participants questionnaires in the trial test. The average of the questionnaire practicality while testing is 3.64 which indicate that the question of SPS is a practical category. The results of the analysis from the expert validation test and learner questionnaire showed the SPS that produced is valid and practical. Keywords: Questions development, science process skill, biology learning material